How did I not see that? Perspectives of nonconsumer mental health researchers on the benefits of collaborative research with consumers. (12th March 2018) - Happell, Brenda; Gordon, Sarah; Bocking, Julia; Ellis, Pete; Roper, Cath; Liggins, Jackie; Platania‐Phung, Chris; Scholz, Brett
Abstract: Coproduction of research between consumers of mental health services and nonconsumer mental health researchers is increasing. There is some research available describing consumer perspectives of this experience. However, there is a notable lack of research on other (nonconsumer) researcher experiences of and views about consumer involvement in coproduced research. A qualitative exploratory study was undertaken to examine perspectives of mental health researchers about consumer involvement in research. In‐depth individual interviews were undertaken with 11 nonconsumer mental health researchers in Australia and New Zealand. Interview transcripts were analysed to identify major themes. There were three interacting themes: the salience of experiential difference, expanded learning, and enhanced research. The dynamic between different perspectives and learning had the effect of enhancing research across the spectrum of study phases and in ensuring research was of value to different groups. The findings emphasize the important contribution consumer researchers can make to mental health research by bringing their unique perspective and enhancing an environment of mutual learning. Findings also point to the need for foregrounding the numerous benefits of joint research between consumer and other researchers to enhance and improve clinical practice and the development of policy.